Prescribing dronedarone for paroxysmal atrial fibrillation: how is it done across the UK and is it safe?. Issue 4 (12th May 2017) - Yones, Eron; Mullan, Jennifer; Horwood, Andrew; Connell, Nicola; Odams, Sarah; Maloney, Jean; Kyriacou, Andreas L; Sahu, Jonathan; Lee, Justin M; Kelland, Nicholas F
Abstract : Dronedarone, a useful treatment for paroxysmal atrial fibrillation, is often only prescribed in secondary care. To support a protocol shared between primary and secondary care, dronedarone use was audited in our centre and prescribing practices across UK secondary care centres were reviewed. From 2010 to 2015, a total of 181 patients were started on dronedarone. There were no deaths or serious adverse events. Median cessation time due to adverse effects was 52 days and 88% stopped dronedarone within 6 months. Of 17 local prescribing protocols across the UK, 12 involved shared care and 5 purely secondary care follow-up. In our review, dronedarone was safe and well tolerated. The use of shared care protocols is well established in other UK centres. The development of a local shared care protocol between primary and secondary care is feasible with existing systems in place to support its introduction.